Transcriptomic analysis revealed that oar-miR-370-3p was involved in the regulation of wool fineness in Ordos fine-wool sheep - Wu, Cuiling; Amar, Gvlnigar; Anwar, Asma; Liu, Wenna; Tang, Sen; Ma, Shengchao; Fu, Xuefeng (Frontiers in Veterinary Science, 2025)
MicroRNA (miRNA) is a prominent topic in biological research, as it plays a crucial role in regulating various physiological processes. Identifying miRNAs associated with fiber traits enhances our understanding of the complex biological mechanisms involved in hair follicle development and provides potential targets for improving fine-wool sheep breeds. This study focused on 20 Ordos fine-wool sheep and identified miRNA expression profiles in skin tissues through transcriptome sequencing. Key miRNAs related to the diameter of wool fibers were preliminarily screened through cell verification experiments. The results revealed 26 differentially expressed (DE) miRNAs in tissues with varying wool fineness, with 12 DE miRNAs being upregulated and 14 DE miRNAs being downregulated. All DE miRNAs predicted 2,844 target genes. Integrating previous mRNA sequencing data, oar-miR-370-3p has 23 differentially expressed target genes. Following the overexpression of miR-370-3p in fibroblasts, the expression levels of the predicted target genes ZDHHC15, JUNB, TGFBI, and IFI6 were upregulated compared to the control group, resulting in increased cell activity. These results provide new insights into the molecular mechanisms regulating the diameter traits of sheep wool fibers and offer important resources for precise sheep breeding research.